Effect of Supplementation of Feed Additives on Haematology and Thyroid Hormones in New Zealand White Rabbits (Indian Journal of Animal Production and Management, 2024)
The present study was conducted on weaned broiler rabbits having similar body weights, which were  divided into four groups with ten rabbits in each group for a period of 42 days. The objective was to  study the effect of inclusion of mannan oligosaccharides (MOS), oxytetracycline and Tulasi (Ocimum  sanctum) supplements in the basal diet on hematology and thyroid hormones in New Zealand white  rabbits. The result revealed that the TEC was observed significantly higher (p
Keywords: Hematology; MOS; Ocimum sanctum; oxytetracycline; rabbit; thyroid hormones